Bulukumba di Tengah Pergolakan DI/TII 1952-1965 - Widia Astuti Ansar; Ahmadin Ahmadin; M. Rasyid Ridha (Pendidikan Sejarah Fakultas Ilmu Sosial Fakultas Ilmu Sosial, 2017)
This paper discusses the background of the DI/TII in Bulukumba, the activity of the DI/TII, as well as the impact of the existence of the DI/TII to the community Bulukumba for a period of 1952-1965. The results showed the existence of the DI/TII in Bulukumba be supported by the state of the geographical area Bulukumba the part of the hills and forests so thick. The demographic with the majority of the Islamic and are strong among the public and DI/TII the factors the existence of the DI/TII in the region. In this study were presented also factor in the Bulukumba in motion DI/TII the leadership of the Kahar Muzakkar. During its existence, a variety of activities be done, among others, kidnapping, robbery on the ground and at sea, the burning of the people's houses, facilities and infrastructure of government, as well as acts of sabotage in the form of the destruction of the bridge, felling trees, digging the road to hamper the mobility which is “enemy” of DI/TII. The impact of the DI/TII in Bulukumba to its velocity of the economy because the closing of the access between “town and village”, education did not good well because most of the teachers and school students were abducted by a gang of DI/TII, the removal of the social strata and activities that deviate from the teachings of Islam. The method used in this study the method of historical research with through four stages, namely : heuristics, the criticism, an interpretation, and historiography. Heuristik is an activity of collecting the history associated with the topic of discussion through research library and an interview. Criticism of the form of criticism external and criticism of internal matters in order to get an authentic. Then the interpretation or the provision of the meaning of the data obtained as to be compiled into the historical facts, which was written into works of history are arranged in chronological order.